Dietary, supplement, and adipose tissue tocopherol levels in relation to prostate cancer aggressiveness among African and European Americans: The North Carolina‐Louisiana Prostate Cancer Project (PCaP). Issue 13 (5th June 2015) - Antwi, Samuel O.; Steck, Susan E.; Su, L. Joseph; Hébert, James R.; Zhang, Hongmei; Fontham, Elizabeth T.H.; Smith, Gary J.; Bensen, Jeannette T.; Mohler, James L.; Arab, Lenore
<x xml:space="preserve">Abstract</x> Background Controversies remain over the safety and efficacy of vitamin E (i.e., α‐tocopherol) supplementation use for the prevention of prostate cancer (CaP); however, associations of different tocopherol forms and CaP aggressiveness have yet to be examined. Methods This study examined whether food intake of tocopherols, vitamin E supplement use, and adipose tissue biomarkers of tocopherol were associated with CaP aggressiveness among African‐American (AA, n = 1, 023) and European‐American (EA, n = 1, 079) men diagnosed with incident CaP. Dietary tocopherols were estimated from a food frequency questionnaire, supplement use from questionnaire/inventory, and biomarkers from abdominal adipose samples measured using high‐performance liquid chromatography. Odds ratios (ORs) and 95% confidence intervals (95%CIs) were estimated from logistic regression comparing high‐aggressive CaP to low/intermediate aggressive CaP, adjusting for covariates. Results Dietary intakes of α‐and δ‐tocopherol were related inversely to CaP aggressiveness among EAs [OR (95%CI), highest versus lowest quartile: α‐tocopherol, 0.34 (0.17–0.69), Ptrend = 0.006; δ‐tocopherol, 0.45 (0.21–0.95) Ptrend = 0.007]. Inverse associations between dietary and supplemental α‐tocopherol and CaP aggressiveness were observed among AAs, though these did not reach statistical significance [OR (95%CI), highest versus lowest quartile: dietary α‐tocopherol, 0.58 (0.28–1.19), Ptrend = 0.20; supplemental α‐tocopherol, 0.64 (0.31–1.21) Ptrend = 0.15]. No significant association was observed between adipose tocopherol levels and CaP aggressiveness [OR (95%CI), highest versus lowest quartiles of α‐tocopherol for EAs 1.43 (0.66–3.11) and AAs 0.66 (0.27–1.62)]. Conclusions The inverse associations observed between dietary sources of tocopherols and CaP aggressiveness suggests a beneficial role of food sources of these tocopherols in CaP aggressiveness. Prostate 75:1419–1435, 2015. © 2015 Wiley Periodicals, Inc.